2013
DOI: 10.3766/jaaa.24.8.11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hearing Aids in Tinnitus Intervention: A Scoping Review

Abstract: The majority of studies reviewed support the use of hearing aids for tinnitus management. Clinicians should feel reassured that some evidence shows support for the use of hearing aids for treating tinnitus, but there is still a need for stronger methodology and randomized control trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 52 publications
3
66
0
1
Order By: Relevance
“…One study has even reported that the degree of tinnitus impact increases with the degree of hearing loss (Mazurek, Olze, Haupt, & Szczepek, 2010). Further, numerous studies have reported that provision of hearing aids for patients with bothersome tinnitus tends to mitigate their reactions to tinnitus (McNeill, Tavora-Vieira, Alnafjan, Searchfield, & Welch, 2012;Searchfield, Kaur, & Martin, 2010;Shekhawat, Searchfield, & Stinear, 2013). The conclusions from all of these studies are based on the assumption that scores on the tinnitus questionnaires indicate distress due to tinnitus alone.…”
Section: Discussionmentioning
confidence: 99%
“…One study has even reported that the degree of tinnitus impact increases with the degree of hearing loss (Mazurek, Olze, Haupt, & Szczepek, 2010). Further, numerous studies have reported that provision of hearing aids for patients with bothersome tinnitus tends to mitigate their reactions to tinnitus (McNeill, Tavora-Vieira, Alnafjan, Searchfield, & Welch, 2012;Searchfield, Kaur, & Martin, 2010;Shekhawat, Searchfield, & Stinear, 2013). The conclusions from all of these studies are based on the assumption that scores on the tinnitus questionnaires indicate distress due to tinnitus alone.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing aids too, although a standard component of usual care, have little quality evidence of effectiveness for tinnitus [18,19] and are only suggested as an option to be considered in the clinical guidelines by Tunkell et al [10]. The present evaluation raises questions on the feasibility of future research on hearing aids.…”
Section: Discussionmentioning
confidence: 84%
“…The lack of standardisation has the benefit of meeting perceived patient need but an evidence-base to support commissioning of this flexible approach is lacking [18,19].…”
Section: Hearing Aids -Questions On Candidacymentioning
confidence: 99%
“…Several therapeutic approaches-including counseling and behavioral therapy (Andersson & McKenna, 2006;Cima, Andersson, Schmidt, & Henry, 2014;Tyler, Stouffer, & Schum, 1989;Wilson, Henry, Andersson, Hallam, & Lindberg, 1998), the provision of hearing aids (Kochkin & Tyler, 2008;Kochkin, Tyler, & Born, 2011;Searchfield, Kaur, & Martin, 2010;Shekhawat, Searchfield, & Stinear, 2013), and sound therapy devices (Hoare, Searchfield, El Refaie, & Henry, 2014;Tyler, Stocking, Secor, & Slattery, 2014)-can be effective for many people.…”
Section: Discussionmentioning
confidence: 99%